(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
The public communication is a multifaceted and articulated field involving the complex of informative actions that the institutional system addresses the citizens both to make them aware of their rights and how to exercise them, and raising their awareness towards general issues (such as health, environmental education, and civil ethics). Over time, this kind of communication increasingly gains a clearer regulatory and operational framework. In Italy, its current meaning arises from the approval of the Costituzione della Repubblica and culminates – following a path parallel to the progressive reform of public administrations – in the law 150/2000 about the discipline of information and communication activities of public administrations, which constitutes the reference regulatory framework that defines its aims and implementation methods. Although from a cultural point of view this legislative change is a significant step towards best practices, many of the visual aspects of public information campaigns reflect a low level of visual literacy. Therefore, it is possible to claim that the pervasiveness of the media and the democratisation of digital production tools and communication channels have not fostered the spreading of high quality images and of effective informative visual campaigns. Except for a few experiences that exemplify an effective linguistic innovation/evolution, nowadays the italian public communication tends to lose its educational role in building the collective visual culture, probably relinquishing one of its most important duties towards the citizen. This paper aims to retrace the main steps of the evolution of the public communication in Italy, critically analyzing some relevant case studies and discussing the most significative current trends.